(untitled) (CIPEEX, 2025)
This paper examines the compatibility between the sovereignty of jury verdicts and setting aside convictions by means of the criminal review action, specifying the prerequisites and limits of this extraordinary remedy so as not to infringe the Jury Court’s constitutional remit. It recognizes sovereignty (Federal Constitution, art. 5, XXXVIII) as a fundamental—yet not absolute—principle and views criminal review (Code of Criminal Procedure, art. 621) as a post-final-judgment safeguard to correct miscarriages of justice upon new evidence of innocence, false evidence, newly discovered facts, or manifest error. The aim is to show how the legal system reconciles the authority of the verdict with the need to correct injustice. Methodologically, it adopts a normative-case-law analysis and examines applications in concrete cases based on the relevant legislation and the protective purpose of review. The findings indicate that criminal review does not replace jurors’ fact-finding; rather, it functions as a safety valve to annul tainted decisions and, where appropriate, order a new jury trial, thereby preserving sovereignty by resubmitting the case to the people. It concludes that review safeguards fundamental rights and the integrity of proceedings by allowing the exceptional correction of evident errors and unjust convictions.